Load dependence of proximal tubular fluid and bicarbonate reabsorption in the remnant kidney of the Munich-Wistar rat. - Maddox, D A (1986)
Studies were undertaken to characterize the pattern of proximal tubular fluid (APRH2O) and bicarbonate reabsorption (APRHCO3) in the remnant kidney of euvolemic Munich-Wistar rats. The remnant kidney rats were placed on a diet containing either low or normal protein. Collections were obtained in the early, mid-, and late proximal convoluted tubule. Single nephron glomerular filtration rate (SNGFR) increased from 40.2 nl/min in controls to 58.8 nl/min in low protein remnant kidney and 78.1 nl/min in normal protein remnant kidney rats. The filtered load of bicarbonate was 1,272, 1,641, and 2,013 pmol/min, in the three groups, respectively. APRH2O and APRHCO3 increased nearly in parallel. Most of the increase in reabsorption occurred in the early proximal tubule. Tubular hypertrophy could account for at least 20-40% of the increase in reabsorption, but the majority of the increase appeared to be a delivery-dependent response similar to that observed in normal rats after an acute increase in SNGFR.